Agent Stitch. A study in slime - Behling, Steve; Rea, Arianna, 1979- (Los Angeles : Disney Press, 2022)
Stitch is good at sniffing out a lot of things, including trouble! After the events of Lilo and Stitch, paranormal mysteries start popping up across the globe. The United Galactic Federation reluctantly assigns the only alien they know up for the task: Experiment 626. Now, Agent Stitch and his friends are sent off to Paris to uncover the disappearance of one of the federations best operatives, Cobra Bubbles, and rumors of a snail-like aliens known as Snailiens spotted in the city.
Inspired by Disney's Lilo & Stitch.
Kirkus Review, April 2022
4.9
3-6
Keywords: Extraterrestrial beings -- Juvenile fiction; Missing persons -- Juvenile fiction; Humorous stories; Extraterrestrial beings -- Fiction; Missing persons -- Fiction; Paris (France) -- Juvenile fiction; Paris (France) -- Fiction; Humorous fiction; Paranormal fiction